Knowledge, Attitude and Practices (K.A.P.) of doctors prescribing Vancomycin in a tertiary care hospital towards Therapeutic Drug Monitoring (T.D.M.) of Vancomycin - Sujeet Bhilwade; Bhaskar Krishnamurthy; Vinayak A; Mahesh Belhekar (Recent Trends in Pharmacology)
Objective: Vancomycin is frequently prescribed to treat infections caused by methicillin-resistant Staphylococcus aureus. Precise dosing through therapeutic drug monitoring is critical for optimising treatment outcomes, minimising toxicity, and reducing antimicrobial resistance. This study assessed the knowledge, attitudes, and practices of clinicians regarding therapeutic drug monitoring of vancomycin at our institution given the low utilisation rate of this service.Methods: Clinicians from the internal medicine and paediatrics departments provided written informed consent for participation. Data on their knowledge, attitudes, and practices regarding vancomycin therapeutic drug monitoring were collected using a pre-validated questionnaire. Responses were analysed using Microsoft Excel version 2406.Results: Of the 126 clinicians who were approached, 100 participated (50 from each department). Most respondents (79%) were postgraduate doctors with one to three years of experience. Although all participants were aware of therapeutic drug monitoring and 92% knew the service was available, the majority primarily recommended therapeutic drug monitoring for antiepileptic drugs. For vancomycin, only 42% regularly suggested therapeutic drug monitoring, 52% identified appropriate sampling timing, and 35% were aware of its therapeutic range. Although 93% acknowledged vancomycin’s adverse effects, with 34% citing nephrotoxicity, only 46% recommended therapeutic drug monitoring in cases of toxicity. The cost of the service was noted as a barrier by 34%.Conclusion: Clinicians were aware of therapeutic drug monitoring but did not have comprehensive knowledge of vancomycin-specific guidelines. Cost and varied opinions on routine therapeutic drug monitoring hindered its implementation.